2016
DOI: 10.1016/j.engstruct.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Multi-hazard system-level logit fragility functions

Abstract: Fragility functions are used to represent the probability of failure of a structure or lifeline system conditional upon a hazard or set of hazards and are essential in the performance-based design process. Continuous lognormal damage fragilities are traditional, but recent formulations have implemented logit transformations from the family of generalized linear models for categorical data with a binary outcome (e.g., failure, no failure). In wind engineering, single hazard parameters derived from correlated va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Recent research into renewable power to enhance green infrastructure suggests that the implementation of micro-grids at the community level may also result in a more robust power system overall. Another approach to system robustness is to add power generation redundancy at the individual building level through building integrated photovoltaic panels and wind turbines [e.g., Wang et al (2016)]. Ideally the recovery of the infrastructure systems should be based upon the expectations and perspectives of the community, rather than the infrastructure operators.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research into renewable power to enhance green infrastructure suggests that the implementation of micro-grids at the community level may also result in a more robust power system overall. Another approach to system robustness is to add power generation redundancy at the individual building level through building integrated photovoltaic panels and wind turbines [e.g., Wang et al (2016)]. Ideally the recovery of the infrastructure systems should be based upon the expectations and perspectives of the community, rather than the infrastructure operators.…”
Section: Discussionmentioning
confidence: 99%
“…In order to obtain fragility models F(Xmax|H1, …Hn) at the system level for power delivery, weather variable data (H1, …, Hn) at the same geographical scale are necessary. For limited hurricane data sets, fragilities of the following logistic regression format were found, based upon previous work by Reed et al (2016): …”
Section: Fragility Models Using Logistic Regressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data-based fragility models have been widely implemented to estimate the probability of collapse or being in or exceeding a specified damage state for buildings subjected to tsunami (e.g., Reese et al, 2007Reese et al, , 2011Koshimura et al, 2009;Suppasri et al, 2012Suppasri et al, , 2013Charvet et al, 2014aCharvet et al, ,b, 2015Muhari et al, 2015) and earthquake (Porter et al, 2007;Tang et al, 2012;Lallemant et al, 2015). Although not specific to building, Padgett et al (2012) empirically modeled damage to coastal bridges along the US Gulf Coast using multivariate logistic regression models, Reed et al (2016) developed a logit fragility model to predict damage for power systems, and Kameshwar and Padgett (2018) developed a wind buckling and storm surge flotation fragility models for oil storage tanks.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar manner, Chiozzi and Miranda (2017) related cracking and crushing of masonry infill walls with masonry and mortar compressive strengths in addition to the SDR. Reed et al (2016) developed fragility curves for electric power lifeline systems subjected to multiple weather hazards. Yazdi et al (2016) demonstrated the applicability of multinomial ordinal logistic regression to produce multivariate fragility curves for reinforced concrete shear walls.…”
Section: Introductionmentioning
confidence: 99%